KEPENTINGAN ARAB SAUDI MEMBERIKAN SUAKA POLITIK KEPADA PENGUNGSI ROHINGYA PADA TAHUN 2015 - Muhamad Anwar; M. Saeri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The conflict that impinged the Rohingya muslims had occured since the fall of Myanmarc to military junta, the muslims in Rohingnya discriminated by the policy that made by the military junta government and resists the muslims in Rohingnya to cross the boundary and being refeugees in case of the discrimination. Saudi Arabia is the country that care to their suffer since in the past and presents had given the asylum to 170 thousand of Rohingya muslims.This research use the Security Theory of Barry Buzan, which the non-military threat cannot to be ruled out because this threat includes religion, ideology and economy. The datas, statements, facts, information, also the arguments in this research use qualitative methods. The analyze level of this research explains the reasons of Saudi Arabia given the asylum to Rohingnya muslims.This research explains the result of the hipothesis is the motivation of Saudi Arabia deliberately gave the asylum to Rohingnya muslim caused by the common ideology among Saudi Arabia and Rohingya muslims, that is ahlussunnah wal jamaah or in exactly Sunni. Saudi Arabia also give the opportunity to Rohingnya muslim to work or gain the profession in labor sector which in these times filled up by foreign workers. Rohingya muslim get their rights such as educations, health facility, and another rights as the citizens of Saudi Arabia itself.Keywords: Myanmar Conflict, Rohingya muslims, refugees, Asylum seeker, Saudi Arabia.